1999
DOI: 10.1111/j.1440-1614.1999.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Signalling pathways in the brain: Cellular transduction of mood stabilisation in the treatment of manic-depressive illness

Abstract: The long-term treatment of manic-depressive illness (MDI) likely involves the strategic regulation of signalling pathways and gene expression in critical neuronal circuits. Accumulated evidence has identified signalling pathways, in particular the family of protein kinase C (PKC) isozymes, as targets for the long-term action of lithium. Chronic lithium administration produces a reduction in the expression of PKC alpha and epsilon, as well as a major PKC substrate, MARCKS, which has been implicated in long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 198 publications
(260 reference statements)
0
31
0
Order By: Relevance
“…Disturbances of intracellular Ca 2 þ signaling can critically affect cellular function due to calcium's essential role in vital cellular processes including gene expression (Ghosh and Greenberg, 1995), neurogenesis and plasticity (Mattson, 2000), and cell death (Szalai et al, 1999). It is of some interest then that lithium acts on several second messenger systems and intracellular signal transducing proteins (Manji et al, 1999;Williams and Harwood, 2000) that are involved in key cellular functions that affect neurogenesis, neuroplasticity, and cell death (Manji et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances of intracellular Ca 2 þ signaling can critically affect cellular function due to calcium's essential role in vital cellular processes including gene expression (Ghosh and Greenberg, 1995), neurogenesis and plasticity (Mattson, 2000), and cell death (Szalai et al, 1999). It is of some interest then that lithium acts on several second messenger systems and intracellular signal transducing proteins (Manji et al, 1999;Williams and Harwood, 2000) that are involved in key cellular functions that affect neurogenesis, neuroplasticity, and cell death (Manji et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Both the adenylate cyclase and phosphoinositide second messenger systems are deeply influenced by lithium, albeit in different manners, including actions on G proteins and protein kinase C (Jope, 1999;Manji et al, 1999). Evidence that lithium inhibits inositol monophosphatase, decreases brain inositol concentrations, and reduces inositol 1,4,5-triphosphate accumulation in rodent cerebral cortex has led to the inositol depletion hypothesis of its mechanism of action.…”
Section: B Lithiummentioning
confidence: 99%
“…28 Calcium signaling is closely linked to the phosphoinositide pathway, and expression of protein kinase C subtypes (PRKCA and PRKCE) and its substrate myristoylated alanine-rich protein kinase C (MARCKS) are reduced in the rat brain after chronic treatment with lithium. 29 Monoamine neurotransmitter receptors, such as alpha2 and beta-1-adrenergic receptors, are coupled to G proteins, which, upon stimulation, activate enzymes in the cAMP-signaling pathway. The gene for regulator of G-protein signaling 4 (RGS4) was initially brought into attention by a microarray study and recently reported to be associated with schizophrenia.…”
Section: Neurotransmission Systemsmentioning
confidence: 99%